Hybrid absorptive-diffusive frequency selective radome - Lv, Qihao (2022)
This article proposes a hybrid absorptive-diffusive frequency-selective radome (AD-FSR) that has a broadband transmission window with wide absorption and diffusion bands located at two sidebands, respectively. The proposed hybrid AD-FSR consists of a resistive sheet and a bandpass frequency-selective surface (FSS) integrated with a coding metasurface separated by a certain distance. The wide absorption band is realized by the combined effect of the resistive sheet and the FSS integrated with a metasurface as a reflector in its lower stopband, while a broad passband is obtained when the electromagnetic (EM) wave penetrates through the resistive sheet in the passband of the FSS. In the upper side of the passband, the EM wave is diffused to reduce the radar cross section (RCS) of the surface by arranging the unit cell of the AD-FSR and its mirror based on the phase cancellation theory. Equivalent circuit and relevant theoretical formulas are utilized to better comprehend the physical mechanism of the proposed hybrid AD-FSR. A design example is then fabricated and measured, and the experimental results show that a broad transmission band is achieved from 6.92 to 13.12 GHz with a minimum insertion loss of 0.43 dB in a wide low reflectivity ( pmb {|S_{11} |}< -10 dB) band from 2.24 to 18 GHz.